Internal structure and recent dynamics of a moraine complex in an alpine glacier forefield revealed by geophysical surveying and Sentinel-1 InSAR time series - Kunz, Julius; Ullmann, Tobias; Kneisel, Christof (Geomorphology, 2022)
This study presents results on the internal structure and recent dynamics of a thrust moraine complex in the Zay Valley (Italian Alps) by means of geophysical surveying and remote sensing time series. Results from electrical resistivity tomography, seismic refraction tomography, ground-penetrating radar as well as a four-phase modeling approach provided detailed information on the internal moraine structure and confirmed the presence of partly ice-rich permafrost within the moraine complex as well as buried massive ice of sedimentary origin within the proximal moraine flank. The use of Synthetic Aperture Radar interferometry (InSAR) enabled the derivation of detailed surface displacement patterns showing subsidence rates of up to 5 cm within a 30-day period (August/September 2020) over the central part of the moraine complex. Further, preliminary InSAR results indicated an eastward displacement back towards the glacier forefield. The comparison of the results from geophysical measurements and InSAR time series suggested a strong relationship between the subsurface conditions and the surface displacement, as highest displacement rates were found over locations with highest ice content. The consistency of the results enables an area wide estimation of subsurface conditions and highlights the benefits from combining geophysical and remote sensing methods.